Legal Accountability for State Financial Misappropriation in Government Procurement Based on Corruption Court Decision Number 11/Pid.Sus-TPK/2025/PN Plg - Jumadi; Sarah Sarah (CV Edujavare Publishing, 2026)
Corruption in public procurement remains one of the most significant challenges to public financial governance in Indonesia, particularly when it results in financial losses to the state through the abuse of authority and non-compliance with contractual obligations. This study aims to analyze the forms of state financial misappropriation and the legal accountability of the defendant based on Corruption Court Decision Number 11/Pid.Sus-TPK/2025/PN Plg. The research employs a normative legal approach using statutory and case approaches. Primary legal materials consist of legislation and court decisions, while secondary legal materials include books, journal articles, and relevant legal doctrines. The collected legal materials were analyzed qualitatively using a descriptive-analytical method. The findings reveal that the misappropriation of state finances occurred through the implementation of construction work that failed to comply with contractual requirements regarding work volume and technical specifications, resulting in substantial financial losses to the state. The court found that the defendant had fulfilled the constituent elements of a corruption offense by unlawfully enriching another party through conduct that caused state financial losses. The decision demonstrates that criminal liability in corruption cases is established not only by proving the existence of state financial losses but also by demonstrating the abuse of authority, breaches of contractual obligations, and the causal relationship between the defendant's conduct and the resulting losses. The study concludes that strengthening internal oversight, ensuring compliance with procurement procedures, and reinforcing the principles of accountability and good governance are essential measures for preventing corruption in government procurement.